LEGISLATION’S PERMISSIVENESS AND THE CREATION OF BRAZILIAN POLITICAL PARTIES (1979-2018) - Maglia, Cristiana (Revista da Faculdade de Direito do Sul de Minas, 2024)
How has legislation affected the creation of political parties since the return to the multiparty system in Brazil? When we discuss the high fragmentation of the Brazilian party system, one of the main reactions is to affirm that the legislation is permissive. In comparative terms, the literature says that it is easy to create a party in Brazil. In this article, we aim to verify this permissiveness using two approaches. The first one is centered on the electoral legislation, whereas the second one focuses on the specific party legislation. The analysis confirms the perspective that rules structure incentives and constraints for the creation of parties, but they did not operate uniformly over time. Rules are a necessary condition to explain the emergence of parties, however, not sufficient. Institutional changes have created windows of opportunity for the creation of parties with relevant impacts on the design of the Brazilian party system.